14, de Jean Echenoz, un récit de guerre à l’épreuve du pathos - Faria, Dominique (2015)
14 is a recently published novel by a French contemporary writer, Jean Echenoz. Having the First World War as its core subject, the text covers the main traditional themes of war novels. Its interest, however, does not lie in what it says about the war, but rather in how the war is told. In fact, 14 points out the main horrors of the war, without engaging in pathos. In order to do so, Echenoz resorts to two groups of techniques, whose main purpose is to lighten the dramatic effect of the war scenes depicted. Surprisingly, the result is a text which recounts the crude horrors of war.